Status of birds of prey in Guinea-Bissau: First assessment based on road surveys - Henriques, Mohamed (2017)
Several studies have reported marked declines in populations of birds of prey across the African continent, including West Africa. However, there are still regions of which virtually nothing is known, as is the case for Guinea-Bissau. Because birds of prey play important roles in ecosystems and several species are threatened, it is important to establish baseline knowledge on their status. This is the first study in the country focusing exclusively on birds of prey. We conducted 1 711 km of roadside transects from mid-February to the end of May 2016, covering most of Guinea-Bissau. In total 4 989 birds of 33 species were counted, of which Hooded Vultures Necrosyrtes monachus were the most common (252 birds per 100 km, the second highest abundance in all the species’ range). Observations outside transects, including during regular field trips throughout the country, particularly between 2012 and 2016, were used as complementary information adding 13 species to the list, and contributing three new species for Guinea-Bissau: Ayres’s Hawk-eagle Hieraaetus ayresii, Booted Eagle Hieraaetus pennatus and Lesser Kestrel Falco naumanni. Most species showed differences in abundance in relation to vegetation cover (based on the normalised difference vegetation index). Apart from Hooded Vultures and White-backed Vultures Gyps africanus, all other raptors in the IUCN Red List were found to be scarce, including other vultures and several medium-to-large eagles.